2021
DOI: 10.3390/children9010015
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sickle Cell Disease on Academic Performance among Affected Students

Abstract: Background: Sickle cell disease (SCD) is a genetic disease that is highly prevalent in Jazan Province, Saudi Arabia, and is mostly characterized by many complications such as vaso-occlusive crises (VOC), acute chest syndrome (ACS) and well-documented neurological complications. These complications may affect patients’ academic performance. Methods: An observational, cross-sectional, retrospective study was conducted in Jazan Province. General and demographic data were collected and questions about academic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In Nigeria, it was reported that children with SCD are missing school and have poor school performance due to the physical impacts of SCD [ 11 , 12 ]. Additionally, in some schools, special labels are placed on the clothes of pupils/students with SCD for easy identification.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, it was reported that children with SCD are missing school and have poor school performance due to the physical impacts of SCD [ 11 , 12 ]. Additionally, in some schools, special labels are placed on the clothes of pupils/students with SCD for easy identification.…”
Section: Discussionmentioning
confidence: 99%
“…SCD is a chronic disease that is highly prevalent in Saudi Arabia, including the Jazan province. We previously investigated how this disease could affect the affected individual’s quality of life and academic performance [ 1 , 12 , 13 ]. Adherence to appointments with the treating physician is crucial for the purposes of managing and anticipating complications that are commonly associated with this disease [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those who were younger than 18 years of age, living outside Jazan province, and diagnosed with haemoglobin disorders other than SCD, and those who refused to participate, were excluded from the study. Data were gathered using an anonymous self-administrated questionnaire obtained from previously published studies [19][20][21]. The data were collected based on the networks of the trained data collectors and investigators of the study.…”
Section: Methodsmentioning
confidence: 99%